Clinical Characteristics and Outcomes of Ocular Cicatricial Pemphigoid: A Cohort Study and Literature Review. Issue 11 (November 2019) - Fremont, Félix; Pelissier-Suarez, Cyrielle; Fournié, Pierre; Porterie, Marie; Thevenin, Anaïs; Astudillo, Léonardo; Paricaud, Kim; Gualino, Vincent; Soler, Vincent; Pugnet, Grégory
Abstract : Purpose: Ocular cicatricial pemphigoid (OCP) is a rare systemic autoimmune disease and a potentially blinding subepithelial blistering disorder. The purpose of this study was to describe the clinical spectrum of the disease and to assess the efficacy and safety of immunosuppressive agents in a cohort of patients with OCP. Methods: We conducted a monocentric retrospective cross-sectional cohort study of all unselected consecutive patients diagnosed with progressive OCP. Ocular and extra ophthalmological involvement as well as histological findings were gathered. Other outcomes were exposures to immunosuppressive agents defined by the use of a particular treatment. For each exposure, success in controlling ocular inflammation was graded as a complete response, response, or failure. Relapses and adverse events (AE) were also recorded. Results: Seventeen patients (34 affected eyes), 35% of whom were women, were included, with an age at diagnosis of 75 ± 11 years. Corneal involvement was diagnosed in 30 of 34 eyes, and 22 of 34 eyes had progressive fibrosing conjunctival involvement. Sixty-two exposures to immunosuppressive agents or biologics were recorded: dapsone, n = 26; mycophenolate mofetil, n = 6; azathioprine, n = 4; cyclophosphamide, n = 10; rituximab, n = 14; and intravenous immunoglobulin, n = 2. Rates of response and of complete response achievement during the first 3 months were 84% and 45%, respectively. Response rates were 100%, 100%, 86%, 85%, and 80% for intravenous immunoglobulin, mycophenolate mofetil, rituximab, dapsone, and cyclophosphamide, respectively. Thirteen percent of those drugs were discontinued because of an adverse event in 4 patients. Conclusions: This study describes the efficacy of immunosuppressants or biologics with an acceptable safety profile for OCP.